Changes in the Oral Mucosa in Leukemia - Asrorovna, Kholboyeva Nasiba; oʻgʻli, Asrorov Makhmud Akmal; oʻgʻli, Khamrokulov Sobir Khaydar (American Journal of Bioscience and Clinical Integrity, 2025)
Leukemids - a general name for focal and diffuse lesions of the skin, subcutaneous tissue, mucous membranes of the genitals and oral cavity, occurring in areas of malignant proliferation of cells of the blood-forming organs and reticular tissue. They are extramedullary foci of hematopoiesis, developing in the dermis when leukemia enters the terminal stage. Lesions manifest themselves in the form of erythema, erythroderma, raised papules, vesicles or bullae of light pink or dark red color, covered with smooth shiny skin, less often with crusts. In the presence of a comprehensive clinical picture of leukemia, the diagnosis of leukemia does not present any difficulties. Radiation and PUVA therapy are used for treatment.